PEMODELAN REGRESI SPASIAL PADA TPT DI DKI JAKARTA, JAWA BARAT, DAN BANTEN TAHUN 2018 - Muhammad Suprapto; Gama Putra Danu Sohibien (Politeknik Statistika STIS, 2020)
Unemployment is a major problem faced in various countries both developed and developing countries. The problem of unemployment is inseparable with regard to the dimensions of region or spatial dependency. The existence of spatial dependency indicates that unemployment rate in a region will be related to unemployment rate of neighboring. This study aims to provide an overview unemployment rate (TPT) and variable expected influence it, get the best model in explaining impact of social and population variables on TPT, and analyze impact of social and population from the best model on TPT also unemployment reations between regions. TPT Visual analysis is done by mapping while to get the best model in explaining the influence of social and population variables on TPT begins with the creation of a multiple linear regression models, Then proceed with the diagnosis of presence spatial effects by using the method of Moran’s I and Lagrange Multiplier (LM) test. The spatial model formed is spatial lag model. The best model formed is Spatial Lag Model with significant independent variables. variables affecting TPT in Jakarta, West Java, and Banten are percentage of population's marital status and percentage of the poor population.